Matthew’s sitz im Leben and the emphasis on the Torah - Viljoen, F. P. (Faculty of Theology, University of the Free State, 2012)
The role of the Torah is the subject of a full scale discussion in the first Gospel. This article investigates the socio-historical setting that produced this text with such an emphasis on Torah observance. To address these issues, the Matthean text is read to discover issues that were prevalent in the community where the text was produced and read. This is followed by an investigation into developments in the broader Jewish society in the second half of the first century C.E. It becomes clear that the Jewish society was fragmented, and this led to an urge to consolidate. During these developments the Torah was used by newly formed communities to define their norms of existence. In the first Gospel the author defines their position terms of specific Torah observance. While countering some form of Christian libertinism and allegations against the Torah observance of his community, he assures his community of their convictions
Keywords: Matthean community; Sitz im Leben; Sermon on the Mount; Judaism